AGE-RELATED DIFFERENCES IN FUNCTIONAL CAPACITY AND TECHNICAL PERFORMANCE IN YOUTH SOCCER PLAYERS WITH SIMILAR TRAINING AGES - Kirmizigil, Berkiye; Chauchat, Jeffry Roy (Dokuz Eylul Univ Inst Health Sciences, 2025)
Purpose: Chronological age is the most straightforward method for classifying youth soccer players based on their date of birth. However, results concerning the effect of chronological age on functional capacity and technical performance are controversial in youth soccer. Therefore, the aim of the present study was to determine the differences in physical and soccer technical performance between U12 and U14 male soccer players with similar training ages. For this purpose, 84 soccer players were grouped according to their soccer age category (U12 and U14). Material and Methods: Body weight, body mass index and body composition were measured by using a bioelectrical impedance analysis. Flexibility, static balance, and vertical jump performances were measured using the sit-and-reach test, Flamingo balance test, and vertical jump test, respectively. Moreover, soccer technical performance was evaluated using Mor-Christian passing test. Results: The mean training ages of the U12 (4.28 +/- 2.14 years) and U14 (5.00 +/- 2.55 years) groups were similar (p = 0.15), whereas their chronological ages differed significantly (U12: 10.46 +/- 0.78 years; U14: 12.09 +/- 0.28 years; p < 0.05). Anthropometric measurements (height, weight and fat free mass), flexibility, static balance, vertical jump, and passing results were significantly higher in U14 compared to U12 soccer players (p<0.05). Conclusion: U14 soccer players demonstrated superior physical and technical performance compared to U12 players, despite similar training ages. These findings suggest that age-related developmental factors play a key role in performance and highlight the need to consider individual maturity and physical characteristics in youth training and classification.
Keywords: Youth soccer; chronological age; training age; technical performance; functional capacity